A novel secure routing protocol of generation and management cryptographic keys for wireless sensor networks deployed in internet of things. (12th January 2021) - Jerbi, Wassim; Guermazi, Abderrahmen; Trabelsi, Hafedh
Sensors are lightweight platforms, with limited computing power and energy reserves. However, our article is all about creating a secure routing protocol that provides reliable communications. The crypto-ECC contributions seek to accelerate the computation of scalar multiplications by using the paralleling technique which consists of distributing the calculation into several independent tasks that can be processed simultaneously by different nodes. This submission tries to design a secure multicast new routing protocol crypto-ECC that allows the generation and management of cryptographic keys and that takes into account the constraints of the wireless sensor networks and internet of things. Finally, the proposed solution will be evaluated using Telosb sensors, in comparison with earlier work. Performance evaluation using the TOSSIM simulator shows that crypto-ECC is scalable, offers secure links, and provides excellent key connectivity.